The History of Muhammadiyah School in Tanjungpinang - Arman, Dedi; Deswita, Meli (Regalia Institute, 2023)
This paper discusses the history of the Muhammadiyah school in Tanjungpinang City. Writing using historical research methods. The data collection was carried out through literature studies and interviews. The Tanjungpinang branch of Muhammadiyah was established in 1939, but the Muhammadiyah school came later. The Junior High School (SMP) was established in 1961. The Muhammadiyah school in Tanjungpinang has experienced a golden age because it was one of the pioneers in the existence of private schools. The formation of the Riau Archipelago Province in 2004 with the capital in Tanjungpinang ironically did not have a positive impact on the development of Muhammadiyah schools. This condition contrasts with the development of Muhammadiyah schools in Batam City which are progressing rapidly. Weaknesses in management in the management of education caused the Muhammadiyah school in Tanjungpinang to experience setbacks. Another reason is that there are Muhammadiyah figures in Tanjungpinang who built and have Islamic educational institutions which are far more advanced and developed than Muhammadiyah schools.